Analysis of the Correlation Between Academic Stress and Mental Health Among Students of University X in 2025 - ainil fitri; Marsatul Jannah (LPPM Universitas Abdurrab, 2025)
Academic stress is a condition that can arise when students are faced with various academic demands, such as preparing final projects, implementing practical exams, high grade standards, and preparing for the world of work. These various pressures have the potential to affect the mental health condition of students. This study aims to analyze the relationship between academic stress levels and mental health in final year health students at University X Pekanbaru in 2025. This study uses a quantitative approach with a correlational design. The research location is at University X Pekanbaru with a population of 49 students. The sampling technique uses total sampling. The instruments used for data collection were the Perceived Stress Scale (PSS-10) and the Self-Reporting Questionnaire (SRQ-20). The results of the analysis showed that most of the respondents experienced a moderate level of academic stress (75.5%). Meanwhile, the mental health condition of the majority of respondents was in the normal category (55.1%). A statistical test using Chi-Square yielded a value of p = 0.004 (p < 0.05), which showed that there was a significant relationship between academic stress levels and students' mental health, especially in final year students. Therefore, it is recommended that educational institutions provide counseling services, stress management education programs, and adequate psychological support to help students deal with academic pressure more adaptively.